Affective disturbances modulate the neural processing of visceral pain stimuli in irritable bowel syndrome: an fMRI study. Issue 4 (2nd August 2009) - Elsenbruch, S; Rosenberger, C; Enck, P; Forsting, M; Schedlowski, M; Gizewski, E R
Abstract : Objective: To address the role of anxiety and depression symptoms in altered pain processing in irritable bowel syndrome (IBS). Design: In this functional magnetic resonance imaging study, the blood oxygen level-dependent (BOLD) response to rectal distensions delivered at previously determined individual discomfort thresholds was assessed. Patients: 15 female patients with irritable bowel syndrome (IBS) and with normal rectal pain thresholds, and 12 healthy women. Measures: The correlation of anxiety and depression symptoms, measured with the Hospital Anxiety and Depression Scale (HADS), with subjective pain ratings and the BOLD response during distension-induced brain activation were analysed within IBS. Group differences in pain-induced brain activation with and without controlling for HADS scores were evaluated. Results: Patients with IBS experienced significantly more pain and discomfort upon rectal distensions in the scanner, despite unaltered rectal sensory thresholds. Anxiety and depression scores were associated with these subjective stimulus ratings, but not with rectal sensory thresholds. Anxiety symptoms in IBS were significantly associated with pain-induced activation of the anterior midcingulate cortex and pregenual anterior cingulate cortex. Depression scores correlated with activation of the prefrontal cortex (PFC) and cerebellar areas within IBS. Group comparisons with the two-sample t test revealed significant activation in the IBS versus controls contrast in the anterior insular cortex and PFC. Inclusion of anxiety and depression scores, respectively, as confounding variables led to a loss of significant group differences. Conclusions: Altered central processing of visceral stimuli in IBS is at least in part mediated by symptoms of anxiety and depression, which may modulate the affective–motivational aspects of the pain response.